Local government expenditure on education and its effect on income inequality at the county level in Chile (2020)
In this paper we analyze the effect of per-capita education expenditure on the distribution of autonomous income among Chilean counties, where income inequality is measured through Gini and Theil indices, and the S80/S20 and S90/S10 ratios. The longitudinal study considers 307 Chilean counties in order to estimate a fractional response Probit model for Gini index and random-effects Tobit models for the remaining indicators of inequality. Main findings indicate that an increasing per-capita education expenditure would reduce the income inequality among Chilean counties. Moreover, the estimates show that the above negative effect is not immediate but it would take from 3 to 5 years in reducing income inequality at the county level. Finally, the evidence suggests that indigenous people in Chile would be exposed to a larger income inequality when the latter is quantified by Theil index.